PERTIMBANGAN HAKIM TERHADAP HAK ASUH ANAK DAN TANGGUNGJAWAB IBU PASCA PERCERAIAN - Lia Magfiroh; Zakki Adlhiyati (Sebelas Maret University, 2025)
This article describes how the judge's basic consideration is in deciding that custody of a minor child falls to the father and knowing what the mother's responsibilities are after the divorce. Apart from that, it is also to find out about the interpretation used by the judge in deciding the case in Decision Number 3733/Pdt.G/2023/PA.Kab.Kdr. Based on this research, the results showed that the judge's basis for determining child custody based on the mediation agreement letter and the mother's post-divorce responsibilities as stipulated in Decision Number 3733/Pdt.G/2023/PA.Kab.Kdr was not in accordance with the mediation agreement letter agreed upon by the parties.